THE GREEN ECONOMY POLICY AND STRATEGY IN DEVELOPING THE CAPITAL CITY OF NUSANTARA - Agus Setiawan; K.P.Suharyono S.Hadiningrat (Yayasan Inspirasi Merah Putih Indonesia, 2024)
The potential for environmental damage due to land clearing and felling of trees in the physical development of the Indonesian National Capital (IKN) requires pro-environmental policies and strategies to become a sustainable world city, including through the implementation of a green economy. The design of this research is exploratory research with a qualitative approach to find and describe green economic policies and strategies which include types of green economic policies, strategies implemented, and the role of each stakeholder in determining green economic policies that can support IKN development. Archipelago. Data analysis carried out narratively resulted in the conclusion that green economic policy consists of 3 pillars, namely economic, social and environmental which has 15 indicators according to the Indonesian Green Economy Index (GEI). The green economy strategy implemented is to utilize human, money, material, machine and method resources effectively and efficiently to implement a green economy. Collaboration between stakeholders is needed with the Nusantara IKN Authority Agency as the leading pentha helix-based sector. The recommendations are: a) Central Government to prepare policies, strategies and action plans, road maps for implementing the green economy nationally; b) The IKN Nusantara Authority Body is the leading depositor in implementing green economy policies in the IKN Nusantara area according to policies, strategies, action plans and road maps in implementing the green economy in line with the vision and objectives of IKN Nusantara in accordance with Law No. 3 of. 2023 and collaborate with stakeholders; and c) Ministries/Institutions and Regional Governments to support the IKN Nusantara Authority Agency in realizing a green economy through coordination, synchronization and synergy.